Service Quality at the Bengkulu City Motor Vehicle Tax Service Unit - Ridianto; Mulyadi (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
This study evaluates service quality at the Bengkulu City Motor Vehicle Tax Service Unit using the SERVQUAL framework. A quantitative descriptive survey was conducted with 50 motor vehicle taxpayers selected through accidental sampling. Data were obtained through direct observation and a five-point Likert-scale questionnaire covering tangibles, reliability, responsiveness, assurance, empathy, and overall taxpayer satisfaction. The findings show that all five service dimensions were rated in the good category. Assurance and empathy obtained the highest mean scores (3.43 each), followed by reliability (3.31), tangibles (3.04), and responsiveness (2.94). The overall SERVQUAL mean was 3.23. Respondents generally appreciated the safety and comfort of the waiting area, the accuracy of officers, procedural clarity, and the assurance provided during transactions. Nevertheless, the lowest responsiveness score indicates that complaint handling, service speed, and consistency in courteous communication still require improvement. Administrative complexity, waiting time, limited mobile-service facilities, uneven digital capability, and the need for stronger service monitoring were also identified as operational constraints. The study concludes that the unit has established a positive service foundation, but sustained improvement in responsiveness, digital integration, staff professionalism, and feedback management is necessary to strengthen taxpayer satisfaction and support voluntary compliance.